Analisis Kesalahan Sintaksis pada Teks Anekdot dalam Buku Cerdas Cergas Berbahasa dan Bersastra Indonesia Kelas X SMA/SMK Kurikulum Merdeka - Fitri Dwi Cahyani (Pusat riset dan Inovasi Nasional, 2025)
Indonesian language has an important role in education, especially in shaping students’ literacy skills through text-based learning. One type of text taught in the Merdeka Curriculum is anecdote text. This study aims to identify and describe the forms of syntactic errors in anecdote texts in the book Cerdas Cergas Berbahasa dan Bersastra Indonesia for SMA / SMK class X. The method used is descriptive qualitative with error analysis approach according to Ellis’ model. The data were collected through listening and note-taking techniques, and analyzed through the stages of identification, classification, and evaluation of errors. The results of the analysis show the existence of various errors, including the use of non-standard words, incorrect word writing, inappropriate diction, excessive word usage, conjunction errors, and punctuation errors. The findings emphasize the importance of improving the quality of language in textbooks, as errors in books can affect students' language skills. Theoretically, this study expands the study of syntactic errors in the narrative text genre. Practically, the results of this study can be a reference for teachers, book writers, and curriculum developers in improving and enhancing the quality of Indonesian teaching materials.